2017
DOI: 10.1016/j.bjm.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Survey of pathogens in threatened wild red-tailed Amazon parrot ( Amazona brasiliensis ) nestlings in Rasa Island, Brazil

Abstract: The red-tailed Amazon parrot (Amazona brasiliensis) is a threatened species of psittacine bird that inhabit coastal regions of Brazil. In view of the threat of this species, the aim of this study was to perform a health evaluation in wild nestlings in Rasa Island, determining the prevalence of enterobacteria and infectious agents according to type of nest. Blood samples were collected from 64 birds and evaluated for antibodies of Chlamydia psittaci by commercial dot-blot ELISA. Cloacal and oropharyngeal swabs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
4
16
1
1
Order By: Relevance
“…Hidasi et al (2013) studied the intestinal microbiota of parrots belonging to different species (Psittaciformes) seized from illegal trade and also found that E. coli was the most prevalent species (33.8%). Vaz et al (2017) detected that 72.7% of wild redtailed Amazon parrot (Amazona brasilensis) nestlings sampled from artificial wooden nests harbored E. coli; however, the authors considered this result within the normal microbiological profile of such birds.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hidasi et al (2013) studied the intestinal microbiota of parrots belonging to different species (Psittaciformes) seized from illegal trade and also found that E. coli was the most prevalent species (33.8%). Vaz et al (2017) detected that 72.7% of wild redtailed Amazon parrot (Amazona brasilensis) nestlings sampled from artificial wooden nests harbored E. coli; however, the authors considered this result within the normal microbiological profile of such birds.…”
Section: Discussionmentioning
confidence: 98%
“…The composition of the enteric microbiota of wild life psittacines is not fully known. In addition, few studies have been conducted with native Brazilian psittacines, emphasizing the importance of research focusing on these species (Alves et al, 2013;Vaz et al, 2017), and therefore, the Pyrrhura griseipectus (Salvadori, 1900), an endemic bird from the Northeast region of Brazil, was chosen as the object of this study. It is found in three areas of the state of Ceará: Ibaretama, Quixadá, and the Baturité Massif (Girão et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to Saidenberg et al (2015), bacteria from the Enterobacteriaceae family are not part of the intestinal microbiota of free-living psittacine birds. However, studies with isolation of E. coli from different sites (cloaca, oropharynx and feces), involving different species of birds, whether free-living or captive, symptomatic or asymptomatic, resulted in the identification of different enterobacteria present in the digestive system (Xenoulis et al, 2010;Davies et al, 2016b;Cunha et al, 2016;Sanches et al, 2017;Vaz et al, 2017), suggesting that, kept in Gram-negative bacteria, especially enterobacteria, was high. All these agents are potentially pathogenic for parrots and can cause systemic infections in other animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…in stool samples from several species of clinically healthy passerines. On the other hand, in parrot studies, Davies et al (2016a) and Vaz et al (2017) reported the presence of Klebsiella pneumoniae, Klebsiella oxytoca, Enterobacter cloacae, Citrobacter freundii and E. coli associated with clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia em aves cativas, embora a presença de psitacídeos portadores de Escherichia fergusonii tenha sido reportada recentemente (Vaz et al, 2017). Por se tratar de um predador de topo de cadeia alimentar, uma das hipóteses é de que esta bactéria possa estar presente em presas menores, aumentando as chances de ingestão por meio da caça.…”
Section: Caracterização De Virulência E Resistência Deunclassified